1999
DOI: 10.1046/j.1365-2826.1999.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Localization and Ontogenetic Development of Inhibin α Subunit in Rat Brain

Abstract: This study examined the immunolocalization and ontogeny of the inhibin-specific alpha subunit in the brain of male rats. Immunohistochemistry using antiserum directed against the mature region of porcine inhibin alpha (1-19, Tyr20) revealed positive reactions in process-bearing cells resembling astroglia in several regions, especially in the dorsal region of the third ventricle, medial and ventral arcuate nucleus, hippocampal dentate gyrus, and layers 1-3 of the cerebral cortex. Generally, inhibin alpha-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Inhibin alpha subunit and activin expression and protein localization in different parts of the brain were shown in previous studies (Roberts et al., 1996; Fujimura et al., 1999). However, the exact function of this protein in the brain is unknown.…”
Section: Discussionsupporting
confidence: 71%
“…Inhibin alpha subunit and activin expression and protein localization in different parts of the brain were shown in previous studies (Roberts et al., 1996; Fujimura et al., 1999). However, the exact function of this protein in the brain is unknown.…”
Section: Discussionsupporting
confidence: 71%
“…128 The inhibin a-subunit has been shown to be expressed in the hypothalamic arcuate nucleus, the hippocampal dentate gyrus, and the cerebral cortex of the rat brain. 133 The specific role of locally produced inhibin and follistatin in these regions of the brain is not known, but they may be responsible for modulating the effects of activin in the paracrine regulation of neuronal outputs. However, despite extensive in vitro evidence that activin can exert effects on GnRH release, in vivo experiments in ACT-RII receptor null mice demonstrated that although signaling through the ACT-RII receptor is critical for FSH homeostasis, it is not essential for GnRH biosynthesis or induction of pituitary GnRHR expression.…”
Section: Regulation Of Gnrh Secretion By Inhibin Activin and Follismentioning
confidence: 99%
“…Cks2 21 . Further, genes related to astrocytic development ( Inha and Bmp5 ) indicate an immature phenotype 22,23 . In line with this, the astrocytes attempt to restore the lack of neurons as indicated by increased levels of Neurod1 , which has been shown to be able to convert astrocytes to neurons 24 .…”
Section: Resultsmentioning
confidence: 99%